"Ein Kind des Verkehrs"?: Über die allmähliche Verfertigung des Rechts am Beispiel der Sicherungsübereignung um 1900 - Czelk, Andrea (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
"Transfer of ownership by way of security is not in the law, but is permissible" - this is a common statement in teaching. Nonetheless, in all political upheavals, methodological theories have referred to the transfer of ownership by way of security as an example of an extra-legal creation of rights. While in the Weimar era it was economic hardship that caused contemporaries to quarrel, with the National Socialists it was "secrecy" - closely linked to criticism of the BGB drafters, who had developed a legislative technique that was simply incompatible with the idea of a "Führer will". Even after the Second World War, various authors such as Franz Wieacker, Karl Larenz, Claus-Wilhelm Canaris and Bernd Rüthers discussed the relationship between legal development and statutory law using the example of chattel mortgages. When the German Civil Code came into force in 1900, doubts about the legitimacy of chattel mortgages led to a discussion of methods that has remained fundamental to the self-understanding of civil law scholarship to this day.